(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The density, M.V., and A.M.V. of copper surfactant derived from fried and unfried sesame and soyabean oils in non-aqueous and non- polar solvent benzene has been determined at constant temperature 298.15 K. Three samples of each oil were taken fresh, after treating at high temperature for 15 minutes and 60 minutes. The results were used to determine to CMC, chain length effect of the surfactant molecule on CMC and solute-solvent interactions. The studies were used to analyze the effect of high temperature treatment on the structure of the oil and molecular changes. The conclusions have been discussed in terms of well-known Masson’s. This helps us to the use of the oils after abuse of frying at high temperature as they have various industrial and biological applications. Colloidal behavior of copper surfactant used in to study of micellar features and their possible uses in agriculture and industries.